Facile synthesis of palladium nanoparticles supported on urea-based porous organic polymers and its catalytic properties in Suzuki-Miyaura coupling - Pengwei Gao; Yongmei Xiao; Zhenhua Dong; Hongguo Pan; Wentao Wang (Journal of Saudi Chemical Society)
By using urea linked porous organic polymers as template, a new nano palladium catalyst with low Pd loading can be easily prepared (1.0 wt% Pd only). Although such less amount of Pd was contained in this new catalyst, it is still an effective catalyst for the Suzuki-Miyaura coupling of aryl iodines and aryl boric acids, affording biphenyl products in excellent yields with outstandingly enhanced turnover numbers (up to 10,536) under green solvent (water). Keywords: Nanoparticles, Porous materials, Palladium, Porous organic polymers, Suzuki Cross coupling